Forensic Engineering- A New Tool for Investigation (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
Forensic engineering is a compendium of the investigative methodologies used by engineers and scientific investigators to evaluate some of the more common types of failures and catastrophic events. In essence, it provides analyses and methods for determining how an entity was damaged and when that damage may have legal consequences. It covers common types of failures, catastrophic events, and losses that forensic engineers routinely assess. The range of topics include wind and blasting damage to structures, vehicular accidents, fires, explosions, hail damage to roofs and exteriors, lighting damage, and industrial guarding accidents. Additionally, it offers an extensive discussion of the scientific method as it applies to forensic science and provides tips on organising and writing an investigative report. The forensic engineer is yet to be used in various roles in India viz. traffic accidents, court proceedings and spot investigation. Here an effort is made to highlight the applications of the subject and to stress the importance of this field in the administration of justice in the Indian scenario.
Keywords: Forensic Engineering; Accident; Reconstruction